Respuesta :

Answer:

y = 2 sqrt(2) - 2 or y = -2 - 2 sqrt(2) thus B. is the correct answer

Step-by-step explanation:

Solve for y:

-y^2 - 4 y + 4 = 0

Multiply both sides by -1:

y^2 + 4 y - 4 = 0

Add 4 to both sides:

y^2 + 4 y = 4

Add 4 to both sides:

y^2 + 4 y + 4 = 8

Write the left hand side as a square:

(y + 2)^2 = 8

Take the square root of both sides:

y + 2 = 2 sqrt(2) or y + 2 = -2 sqrt(2)

Subtract 2 from both sides:

y = 2 sqrt(2) - 2 or y + 2 = -2 sqrt(2)

Subtract 2 from both sides:

Answer: y = 2 sqrt(2) - 2 or y = -2 - 2 sqrt(2)